Varautuminen ja palautuminen kiristyshaittaohjelmahyökkäyksestä organisaation näkökulmasta - Toivola, Petteri (2024)
This thesis explores the organizational strategies for preparing for and recovering from ransomware attacks. Ransomware incidents have become increasingly prevalent, posing significant threats that can result in severe financial losses and business disruptions. The primary objective of this research is to provide practical solutions and recommendations that organizations can adopt to develop robust recovery plans and ensure business continuity in the event of such attacks.